Moby Dick, or, The white whale - McCaughrean, Geraldine; Melville, Herman, 1819-1891.; Ambrus, Victor G. (Oxford : New York : Oxford University Press, 1996)
A young seaman joins the crew of the whaling ship Pequod, led by the fanatical Captain Ahab in pursuit of the white whale Moby Dick.
Keywords: Whaling -- Fiction; Whales -- Fiction; Sea stories